(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Our work tries to demonstrate how the Roman onomastica is not only a point of arrival, but it also penetrates in the onomastic indigenous forms in languages different from Latin. This is an acculturation process depper and faster, far from being simply the fact known as interpretatio Romana.